KAJIAN STILISTIKA DALAM NOVEL TENTANG KAMU KARYA TERE LIYE - Petronela Osiana Titin; IGA Putu Tuti Indrawati; I Komang Widana Putra (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
The purpose of this study is to describe the style of language used by Tere Liye in the novel About You and to explain the dominant style of language used by Tere Liye in the novel About You. This research is a qualitative descriptive study that discusses language style. Data collection methods in this study are documentation, reading, recording, and selecting data. The steps in analyzing the data are, (1) reading in depth the novel About You by Tere Liye to find out the contents as a whole, (2) understanding the contents of the novel based one language style, (3) recording data in the form of words, sentences, expression, and statements related to language style, (4) date are grouped based on research problems, (5) describe the style of the novel in the novel About You by Tere liye, (6) analyze the style of the novel in the novel About You by Tee Liye, and (7) make conclusions about the analysis of literary works in novels. Based on the results of the research, it can be concluded that the novel About You uses several language style, namely (1) comparative language style includes Juperbola, metonomia, simile and association, (2) repetition language style includes mesodiploss and anaphora. (3) the language style of opposition includes antithesis, and (4) the language style of affirmation includes epiphora. The dominant language style used in the novel About You is anaphora.